MO485PREVALENCE OF ANALGESICS USE AND ASSOCIATED ADVERSE OUTCOMES IN THE CHRONIC KIDNEY DISEASE POPULATION: A SYSTEMATIC REVIEW AND META-ANALYSIS*. (29th May 2021) - Lambourg, Emilie; Colvin, Lesley; Guthrie, Greg; Walker, Heather; Bell, Samira
Abstract: Background and Aims: Pain is one of the commonest symptoms in patients with chronic kidney disease (CKD), with a large proportion undertreated. Managing chronic pain in CKD patients is problematic due to the altered pharmacokinetic and pharmacodynamic related to the reduced renal clearance making it challenging for physicians to find appropriate pain management strategies. The aim of this systematic review was to estimate the overall prevalence of different types of analgesia in patients with CKD and investigate their safety. Method: The population comprised of all adult patients with CKD defined as an estimated glomerular filtration rate (eGFR) less than 60mL/min/1.73m 2 which included CKD-non dialysis (CKD-ND), kidney transplant recipients (KTR), patients undergoing dialysis and those receiving palliative care. Analgesics investigated included opioids, Nonsteroidal Anti-Inflammatory Drugs (NSAIDs), gabapentinoids and acetaminophen. All studies reporting a prevalence of analgesic use and/or exploring the association between analgesic consumption and adverse outcomes were included. Medline, Embase, CENTRAL, CINAHL and the grey literature were searched up to December 2020. Random-effect meta-analyses were conducted using a Generalised Linear Mixed Model approach to estimate the overall prevalence of analgesics use in the CKD population, displayed in forest-plots. Evidence gathered from studies investigating the adverse outcomes related to analgesics consumption was synthesised in 'harvest plots'. Results: Sixty-three studies reporting a prevalence of analgesic use in patients with CKD were included. The overall prevalence of analgesic consumption was 42% (95% CI, 35-50%) in the general CKD population and 70% (95% CI, 62-68%) among those experiencing chronic pain. Seventeen studies reported a prevalence of opioid use with 36% (95% CI, 23-51%) of patients with CKD receiving at least one opioid prescription while 16% (95% CI, 11-22%) were on chronic opioid therapy. The chronic use of oxycodone, tramadol, propoxyphene, fentanyl and hydromorphone were 3.6%, 2.0%, 1.3%, 1.1% and 0.05% respectively. NSAIDs usage was estimated to 20% (95% CI, 15-25%) among patients with CKD (ibuprofen 4.6%, diclofenac 1.7%) and 8% (95% CI, 5-12%) took NSAIDs chronically, with a higher prevalence among dialysis patients (17%) compared with CKD-ND (7%) and KTR (5%) (p<0.01). Prevalence of gabapentin and pregabalin use was estimated at 10% and 3.5% respectively, on pooling of 3 studies. Finally, five studies yielded an overall prevalence of 24% for acetaminophen use. Twenty studies assessing the association between analgesic use and adverse outcomes were included (Figure 1 ). Five of them demonstrated an association between opioid use and increased mortality, in all CKD subgroups; and three out of four studies reported more hospitalizations in opioid-users.Four studies highlighted an increased risk of gastro-intestinal bleeding associated with NSAIDs consumption and three studies found a significant association between gabapentin use and neurologic adverse events. Conclusion: Only 70% of CKD patients experiencing chronic pain received an analgesic, suggesting that pain remains a significant public health burden. Despite limited evidence, opioids, NSAIDs and gabapentinoids seem to be associated with major adverse events. Their use requires cautious prescription, consideration of optimal dosage, and the development of therapeutic patient education to promote risk awareness. More evidence is warranted to better understand the adverse outcomes associated with long-term analgesic consumption and provide safe pain management strategies for patient with CKD.